A gestão do conhecimento sob o enfoque do comportamento de busca informacional do indivíduo no processo decisório - Garcia, Regis [UNESP]; Clemente, Ademir; Olak, Paulo A.; Fadel, Bárbara [UNESP] (My University, 2010)
The discussion of organizational knowledge management requires theoretical base and proposals based on empirical evidence. There is a risk not consider it as part of a larger process, responsible for the move of all the organizational environment, it means decision process. From the analysis of behavior in seeking information tied to a specific problem of decision - the shift from analogue to digital by the Brazilian photographic business - aims to help strengthen the arguments that is not only possible but desirable the action focused on knowledge management in organizations, especially mediation, constant and intentional. It appears as main results the confirmation that the information available and the behavior of the individual search result in the generation of knowledge, according to decision theory, and thus it would be inconceivable the omission of an effective action for mediation as part of their management.
Knowledge management focusing the behavior of the individual information search in the decision process
Keywords: Behavior; Decision; Decision process; Information flux and mediation; Knowledge; Knowledge management